Germ wars : the politics of microbes and America's landscape of fear - Armstrong, Melanie, 1977- (Critical environments. Nature, science, and politics., 2017)
"The United States government has spent billions of dollars to prepare the nation for bioterrorism despite the extremely rare occurrence of biological attacks in modern American history. Germ Wars argues that bioterrorism has emerged as a prominent fear in the modern age, arising with the production of new forms of microbial nature and changing practices of warfare. In the last century, revolutions in biological science have made visible a vast microscopic world, and in this same era we have watched the rise of a global war on terror. Germ Wars demonstrates that these movements did not occur separately but are instead deeply entwined--new scientific knowledge of microbes makes possible new mechanisms of war. Whether to eliminate disease or create weapons, the work to harness and control germs and the history of these endeavors provide an important opportunity for investigating how biological natures shape modern life. Germ Wars aims to convince students and scholars as well as policymakers and activists that the ways in which bioterrorism has been produced have consequences for how people live in this world of unspecifiable risks"--Provided by publisher